Flash Gordon : space soldiers conquer the universe - Beebe, Ford; Taylor, Ray, 1888-1952; Plympton, George H.; Dickey, Basil, 1880-1958; Shipman, Barry, 1912-1994; Crabbe, Buster, 1908-1983; Raymond, Alex, 1909-1956.; King Features Syndicate; Cinetel Films ([North Hollywood, CA] : Universal Pictures Company, Inc., 1940)
Flash Gordon battles Emperor Ming in order to restore the planet Mongo to its rightful ruler, Prince Baron.
Chapter 3: Walking bombs -- Chapter 4: The destroying ray -- Chapter 5: The palace of peril.
Flash Gordon conquers the universe originally released as a motion picture serial in 1940.
Based on the newspaper feature by Alex Raymmond, entitled "Flash Gordon."
Larry (Buster) Crabbe, Carol Hughes, Charles Middleton, Anne Gwynne, Frank Shannon.
Cinematographers, Jerome Ash, William A. Sickner; editors, Albin Todd, Louis Sackin, Joseph Glick.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed November 25, 2015).
Keywords: Gordon, Flash (Fictitious character) -- Drama; Heroes -- Drama; Good and evil -- Drama; Planets -- Drama; Superhero television programs; Science fiction television programs; Action and adventure television programs; Internet videos; Streaming video